Development of Problem-Based Learning Multimedia to Improve the Learning Outcomes of Students of Digestive System Materials in Humans - Audianna Najwa Kournikova; Aldina Eka Andriani (Pusat Publikasi Ilmiah, STKIP Taman Siswa Bima, 2026)
The learning outcomes of students in the material of the digestive system in humans are relatively low. The purpose of this study is to design a development design, test the feasibility and effectiveness of Problem Based Learning-based multimedia on digestive system materials in human class V SDN 2 Nolokerto, Kendal Regency. This research procedure uses an R&D (Research & Development) model. Data collection techniques used tests (pre-test and post-test) and non-tests (observation, interviews, questionnaires, and documentation). The data analysis test used the normality test, the paired sample t-test, and the N-Gain test. The results of the research in the form of a Problem Based Learning-based multimedia development design developed with Canva consist of usage instructions, activity instructions, materials that include text, images, videos, quizzes (wordwall) and are equipped with a virtual gizmos laboratory. The feasibility of Problem-Based Learning-based multimedia is shown by the assessment of material experts of 92.85% and media experts of 91.07% with the category of very feasible. It was supported by a teacher response questionnaire of 95% and received a response from students of 95.38% with the category of very feasible. The average pre-test score was 53.97 and the post-test average increased to 76.79 with an increase of 22.79. The results of the N-Gain test obtained an average value of 0.4 in the medium category. The conclusion of this study shows that this Problem Based Learning-based multimedia has been successfully developed, feasible and effective to improve student learning outcomes on the material of the digestive system in humans.